EPIDEMIOLOGICAL PROFILE OF PALATAL AND MANDIBULAR TORI IN A SUBPOPULATION FROM NORTHERN BRAZIL (REMUNOM, 2025)
Tori are benign bony exostoses that affect the maxilla and mandible, characterized by a dense outer layer of cortical bone and an inner region of medullary bone. Although they are not considered pathologies, they may require surgical intervention if they cause difficulties in chewing, swallowing or using prostheses. The objective of this study was to evaluate the epidemiological profile of patients treated at the propaedeutic dental clinic at the Federal University of Pará, analyzing the association between torus and the variables: sex, color and age group. A cross-sectional analytical study with a quantitative approach was carried out, using data from 1200 patients treated between January 2018 and December 2023. The results obtained showed that 29.83% of the study population had torus, with the highest prevalence being females (74%). Regarding color, 67% were black (association of black and mixed race). In terms of age, the most prevalent age group was 20 to 29 years old, representing 25.4% of all cases. Understanding these epidemiological patterns is essential for the appropriate diagnosis and treatment of these benign conditions, highlighting the importance of clinical and radiographic assessment to determine the need for clinical intervention.